E-LEARNING MENGGUNAKAN EDMODO BERBASIS SOCIALIZATION MODEL SECI - Kristiani, Dwi (JITU, 2018)
Kurikulum 2013 is a kind of learning model which the students should be active and the teacher should becreative when delivers the lesson to her/his students. Delivering the teaching material in any methods is expectedthe students can understand the material easily and aren’t bored while the lesson. As we know that by kurikulum2013, the students must spend to study at school until a half to four in the afternoon. It makes the teachinglearning process can’t be effective. The students’ concentration disturbed caused they are tired. By the conditionabove, a teacher needs to have a teaching method that is interested in teaching learning process to the students.E-learning process in the teaching learning process based on Fase Socialization in SECI model is made by thewriter to help the teacher in giving the learning material in the different way. From the result of the researchshows that there are kompetensi Dasar which can plot based on Fase Socialization. The use of Edmodo canimprove the student learning outcomes and also help teacher to organize the individual task or group of thestudents.